HYPERBOLE, EXPRESSING CULTURAL CONNOTATIONS IN THE UZBEK LANGUAGE (American Journal of Research in Humanities and Social Sciences, 2024)
The scientific article is determined by the following key factors: the increasing interests in exploring the issues of linguistics of Uzbek languages in harmony with language features; the study of stylistic devices has become an important aspect of cognitive linguistics investigations; revealing linguistic specificity and complexity of Stylistics has acquired both theoretical and practical significance for further study of the principles and mechanisms characterizing the development of its verbalization; Explain the international cultural features of hyperbole and the influence of folk culture on its use.